PENGARUH PROMOSI ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN STAYCATION DI UBUD DAN CANGGU - Valineli, Samantha Elana; Agus Wikanatha Sagita, Putu; Kristianto, Yohanes (Jurnal IPTA, 2023)
This study aimed to determine whether E-WOM had an influence on staycation decisions in Ubud and Canggu. This study determined the sample by purposive sampling method with a total sample of 100 respondents. Data collection used a questionnaire, literature study, and documentation. The data analysis technique in this research is descriptive quantitative with validity test, reliability test, classical assumption test, linear regression analysis, t test, and coefficientdetermination test. This study used the IBM SPSS statistics 25 for Windows program to carry out research tests. The results of the analysis showed that E-WOM quality had t count 2.027 > t table 1.988 with a significance value of 0.047 > 0.05, then E-WOM quantity had t count 2.113 > t table 1.988 with a significance value of 0.037 <0.05 then Sender’s expertise variable had t count 3.447 > t table 1.988 with a significance value of 0.001 <0.05. These results showed that the variables E-WOM quality, E-WOM quantity and Sender’s expertise influence the staycation decision. The results of this study also showed that E-WOM has a significant simultaneous effect on staycation decisions in Bali with a coefficient of determination of 65%.